An assessment of Project-Based Learning towards Applied Health Informatics Teaching in an Undergraduate Class - Santos, Lidiany Cerqueira; Neves, Danilo Ferreira; Menezes, Fabrício dos Santos (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2020: Anais do XXXI Simpósio Brasileiro de Informática na EducaçãoDO - 10.5753/cbie.sbie.2020.202, 2020)
This study aims to report and evaluate teaching based on Project-Based Learning towards an undergraduate subject of Applied Health Informatics. As an evaluation method, the development of mobile health applications was proposed. The research was conducted in a class with 21 students, who were evaluated qualitatively by two surveys. The students reported a positive impact of the discipline on their training and improvement in computational thinking abilities. Overall, the students created six m-health applications, and they achieved a new technology perception. Moreover, 15 students (71.4%) said to be more motivated to learn new technologies and 16 (76.2%) reported to be able to develop new applications.